Effect of two natural biostimulants on the production of two varieties of Rose (Rosa Sp.) under greenhouse in the Quiquijana district in Cusco – Peru - Sovia Hancco, Reyna (2024)
Objective: To determine the effect of two natural biostimulants on the production of two varieties of rose (Rosa sp.) under greenhouse in the Quiquijana district of Cusco-Peru. Method. It was carried out in a greenhouse at an altitude of 3,053 meters above sea level. The completely randomized design (DCA) was used with a 2 x 3 factorial arrangement and three repetitions; Factor a: Variety (a1: Freedom and a2: Gold strike) and Factor b: biostimulant (b0: Without biostimulant, b1: Natural biostimulant and b2: Foliar biostimulant with algae extract). Results, applying the natural biostimulant, the stem length reached 95.52 cm on average. In stem diameter (variety Rojo Freedom) it reached 27.63 mm and with biostimulant 9.22 mm. For flower bud height (variety Rojo Freedom) it reached 34.36 cm and with natural biostimulant 39.67 cm; For the flower bud diameter (Red Freedom variety) it reached 28.55 mm and with natural biostimulant 34.23 mm. Conclusion. The Biostimulants induced better quality indicators in the production of roses both in stem properties, flower bud development and profitability.